Efficacy of tedizolid against enterococci and staphylococci, including cfr+ strains, in a mouse peritonitis model (2019)
In a mouse peritonitis model, tedizolid was comparable to linezolid and daptomycin against an Enterococcus faecium strain (VANr, AMPr), an Enterococcus faecalis strain, and a methicillin-resistant Staphylococcus aureus (MRSA) strain with and without cfr. Against a cfr(B)+ E. faecium, tedizolid was inferior in vivo to linezolid and daptomycin, despite an ∼4-fold lower MIC.